Accuracy Level of Backpropagation Algorithm to Predict Livestock Population of Simalungun Regency in Indonesia. (August 2019) - Purba, Indri Sriwahyuni; Wanto, Anjar; Riansah, Reza Muhammad; Ahmad, Yogi; Siregar, Sandy Putra; Winanjaya, Riki; Julham, Mhd.; Silitonga, Hotmalina
Abstract: The development of livestock agribusiness includes all activities that begin with the procurement and regulation of production and marketing suggestions. With the many types of livestock found in Simalungun Regency, Indonesia should be able to increase the potential for livestock agribusiness development. In this study, the authors will analyze the best architecture that can be used to predict the number of livestock populations according to the type of livestock in Simalungun District Indonesia so that certain parties can make improvements to the development of livestock agribusiness in Simalungun District Indonesia. In this study, there are five 5 architectural models namely, 3-5-1 architecture, 3-6-1, 3-7-1, 3-8-1, and 3-9-1. Of the five architectural models, the best architectural model is 3-7-1 with 75% accuracy and 1693 epoch. While the error rate is 0.001-0.01. It is expected that this architectural model can help academics in the process of predicting the number of livestock populations in Simalungun Regency in the coming year.